Star wars episode III : revenge of the sith - Wrede, Patricia C., 1953-; Lucas, George, 1944- (New York : Scholastic, 2005)
Anakin Skywalker and Obi-Wan Kenobi heroically try to defend the Republic from the attacks of the Separatists.
"Lucas books."
Keywords: Vader, Darth (Fictitious character) -- Juvenile fiction; Kenobi, Obi-Wan (Fictitious character) -- Juvenile fiction; Good and evil -- Juvenile fiction; Space warfare -- Juvenile fiction; War -- Fiction; Science fiction; Star Wars fiction; Science fiction; Movie novels